2016
DOI: 10.1111/1541-4337.12222
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Heracleum: A Comprehensive Review on Its Phytochemistry, Pharmacology, and Ethnobotanical Values as a Useful Herb

Abstract: Heracleum species, also known as hogweed, are traditionally used as food additives, spices, and flavoring agents. Moreover, these plants are widely used in folklore medicine for the treatment of many disorders such as inflammation, flatulence, stomachache, epilepsy, psoriasis, and as carminative, wound healing, antiseptic, antidiarrheal, tonic, digestive, pain killer, analgesic, and anticonvulsant agents. The genus Heracleum has broad pharmacological activities: anti-inflammatory, antimicrobial, anticholineste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 118 publications
0
42
0
Order By: Relevance
“…Coumarins possess a variety of biological properties, such as antioxidant, and enzyme inhibitory activity [1]. So, it might be responsible for bioactivity of the different parts of the methanolic extracts of the H. platytaenium plant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coumarins possess a variety of biological properties, such as antioxidant, and enzyme inhibitory activity [1]. So, it might be responsible for bioactivity of the different parts of the methanolic extracts of the H. platytaenium plant.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Heracleum, one of the broader classes of the Apiaceae family, is represented by approximately 125 species worldwide and are known to contain flavonoids, coumarins and triterpene saponins [1]. Heracleum is represented by 109 species in Asia with 23 species found in Turkey among which 9 are endemic [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes the outer flowers of the umbel are much larger than the inner ones. [29] Traditional uses i) Used to make poultices to be applied to bruises or sores.…”
Section: Plant Descriptionmentioning
confidence: 99%
“…The fruits of Golpar is used as flavoring agent and dietary spice in the Iranian cuisine and the young stems are used for making pickles. Furthermore, it is utilized for miscellaneous remedial purposes including carminative, anticonvulsant, analgesic, cure of neurological, urinary tract and gastrointestinal problems in the Iranian traditional medicine (Bahadori et al, ; Dadjo et al, ; Majidi & Sadati Lamardi, ; Panahi, Dadjo, Pishgoo, Akbari, & Sahebkar, ). Pharmacological studies have demonstrated a wide range of biological activities including anti‐bacterial (Akcin, Seyis, Akcin, Cayci, & Coban, ; Atapour et al, ; Buruk, Sokmen, Aydin, & Erturk, ; Kousha & Bayat, ; Vasanthi, ShriShri Mal, & Das, ), anti‐fungal (Kousha & Bayat, ; Nejad, Rajabi, Mamoudabadi, & Zarrin, ; Vasanthi et al, ), anti‐proliferative (Firuzi, Asadollahi, Gholami, & Javidnia, ; Moshafi, Sharififar, Dehghan, & Ameri, ), anti‐inflammatory (Hajhashemi, Sajjadi, & Heshmati, ; Panahi et al, ), immune‐modulatory (Naeini, Shokri, & Khosravi, ; Sharififar et al, ), antioxidant (Coruh, SagˇdıçogˇluCelep, & Özgökçe, ; Nickavar & Abolhasani, ), analgesic (Hajhashemi et al, ), and lipid‐modifying (Panahi et al, ) properties.…”
Section: Introductionmentioning
confidence: 99%